Hospital differences in rates of cesarean deliveries in the Sardinian region: An observational study - Massimo Cannas; Emiliano Sironi (Epidemiology, Biostatistics and Public Health)
Background: The rates of cesarean deliveries have been increasing steadily in several European countries in recent decades, with Italy having the second-highest rate (38% in 2010), causing concern and debate about the appropriateness of many interventions. Moreover, some recent studies suggest that rates of common obstetric interventions are not homogeneous across hospitals, maybe not only because of patient case mix but also possibly because of different hospital practices and cultures. Thus, it is important to investigate whether the variation in rates of cesarean sections can be traced back to patient characteristics or whether it depends upon context variables at the hospital level.   Objective and method: Using official hospital abstracts on deliveries that occurred in Sardinia over a two-year period, we implement multilevel logistic regression models in order to assess whether the observed differences in cesarean rates across hospitals can be justified by case-mix differences across hospitals.   Results: The between-hospital variation in rates of cesarean delivery is estimated to be 0.388 in the model with only the intercept and 0.382 in the model controlling for the mother’s clinical and sociodemographic characteristics.   Conclusions: The results show that taking into account the individual characteristics of delivered mothers is not enough to justify the observed variation across hospital rates, suggesting the important role of unobserved variables at the hospital level in determining cesarean section rates.